1966
DOI: 10.1071/ar9660885
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic characteristics of Rhizobium meliloti: and appraisal of the systematic treatment of nodulation and nitrogen fixation interactions between hosts and Rhizobia of diverse origins

Abstract: The symbiotic properties of 42 isolates of Rhizobium meliloti collected from widely separated sites in the upper basin of the Darling River were tested in bacteriologically controlled culture with 18 species and varieties of Medicago, three species of Melilotus, and one species of Trigonella. Seven strains of Rh. Meliloti of commercial interest were included in the experiments for comparative purposes. Nodule formation occurred on all plants in 889 out of 974 symbiotic combinations examined. Only Medicago laci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 0 publications
0
42
1
Order By: Relevance
“…While most Medicago species nodulated and formed nitrogen-fixing symbioses when they were grown in Australian soils with naturalized rhizobial populations, Ballard and Charman (3) observed that there was a lower incidence of nodulation with M. laciniata. They attributed this observation to the specific rhizobial requirement of M. laciniata that had been reported previously by Brockwell and Hely (7). For nodulation of M. laciniata, Brockwell and Hely (7) suggested that its rhizobia have distinct nodule formation behavior that distinguishes them from other Medicago-nodulating rhizobia.…”
mentioning
confidence: 75%
“…While most Medicago species nodulated and formed nitrogen-fixing symbioses when they were grown in Australian soils with naturalized rhizobial populations, Ballard and Charman (3) observed that there was a lower incidence of nodulation with M. laciniata. They attributed this observation to the specific rhizobial requirement of M. laciniata that had been reported previously by Brockwell and Hely (7). For nodulation of M. laciniata, Brockwell and Hely (7) suggested that its rhizobia have distinct nodule formation behavior that distinguishes them from other Medicago-nodulating rhizobia.…”
mentioning
confidence: 75%
“…These results were compiled from the results of the current study (see Table S3) and also from the results from three previous studies (4,7,9). In general, members of the T. suavissima strain clade (CST Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The strain possessing this genotype was USDA6670 (syn., CC2013), a strain symbiotically effective with the native Australian legume Trigonella suavissima Lindl. (4). In subsequent studies, four other T. suavissima symbionts were also described as having multilocus genotypes similar to that of USDA6670 (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, suitable herbaceous legumes are needed as pasture components in lower rainfall regions and for those parts of the country likely to become hotter and dryer in the future. The symbiotic root nodule bacteria for introduced legume species are widespread within these parts of the country (Brockwell and Hely 1966;Khu 1969). The domestication of some of the native herbaceous legumes may fill this need.…”
Section: Forage Legumesmentioning
confidence: 99%